Politik Bahasa "Jawa Anyar" dalam Ranah Pendidikan - Restu Rahmawati (Journal of Politics and Policy, 2019)
This study examines about Political language of Jawa Anyar in education on the local content curriculum in Banyumas. The purpose of this study was to clarify the chronological occurrence of the Political language of Jawa Anyar on the local content curriculum in Banyumas, and to evaluate the response of Banyumas community associated with the implementation of the political language. The method used in this study is qualitative descriptive analysis. The study results that first, the political language caused by construction and reconstruction of the Political language of Jawa Anyar. The political manifestation of the Political language of Jawa Anyar is due to policy of local local content curriculum at all levels of public education in Banyumas regency. Secondly, the political response of Banyumas community to the Political language of Jawa Anyar is through resistance action as practiced by the school parties, e.g., principal, teachers, students, and cultural community of Banyumas. Third, as a theoretical reflection on the field findings, the author argues that political language is actually the only kind of reduction in the participation of minority language groups.Therefore, the planning effort of Political language of Jawa Anyar as the interest of state apparatus has reduced the participation of minority language groups; in this case, it reduces participation of Banyumas language community.